Contribution of congenital heart disease to neuropsychiatric outcome in school‐age children with 22q11.2 deletion syndrome. Issue 2 (22nd November 2013) - Yi, James J.; Tang, Sunny X.; McDonald‐McGinn, Donna M.; Calkins, Monica E.; Whinna, Daneen A.; Souders, Margaret C.; Zackai, Elaine H.; Goldmuntz, Elizabeth; Gaynor, James W.; Gur, Ruben C.; Emanuel, Beverly S.; Gur, Raquel E.
<x xml:space="preserve">Abstract</x> Children with 22q11.2 deletion syndrome (22q11DS) present with congenital heart disease (CHD) and high prevalence of psychiatric disorders and neurocognitive deficits. Although CHD has been implicated in neurodevelopment, its role in the neuropsychiatric outcome in 22q11DS is poorly understood. We investigated whether CHD contributes to the high prevalence of psychiatric disorders and neurocognitive impairments in 22q11DS. Fifty‐four children ages 8–14 years with 22q11DS and 16 age‐matched non‐deleted children with CHD participated. They were assessed using semi‐structured interviews and a Computerized Neurocognitive Battery. CHD status was assessed using available medical records. Prevalence of psychiatric disorders and cognitive profiles were compared among the groups. There were no significant differences between the prevalence of psychiatric disorders in the 22q11DS with and without CHD. In 22q11DS with CHD, the prevalence rates were 41% anxiety disorders, 37% ADHD and 71% psychosis spectrum. In 22q11DS without CHD, the rates were 33% anxiety disorders, 41% ADHD and 64% psychosis spectrum. In comparison, the non‐deleted CHD group had lower rates of psychopathology (25% anxiety disorders, 6% ADHD, and 13% psychosis spectrum). Similarly, the 22q11DS groups, regardless of CHD status, had significantly greater neurocognitive deficits across multiple domains, compared to the CHD‐only group. We conclude that CHD in this sample of children with 22q11.2DS does not have a major impact on the prevalence of psychiatric disorders and is not associated with increased neurocognitive deficits. These findings suggest that the 22q11.2 deletion status itself may confer significant neuropsychiatric vulnerability in this population. © 2013 Wiley Periodicals, Inc.